Theoretical Aspectrs of Integrating Non-Finance Information in Corporate Accounting - L. M. Korchagina (Вестник Российского экономического университета имени Г. В. Плеханова)
Today it is very important to maintain confidence of concerned parties at all levels, as the lower confidence, the higher stimulus is to change the partner or producer. Since the late 20th century non-finance accounting became more and more significant due to internationalization, digitalization and growing role of intangible assets in company capitalization. Non-finance accounting includes ecologic, social and managerial information. Sustainable development and non-finance information have become the key problem among business leaders, investors and regulation bodies. Participants of capital market pay higher attention to the importance of non-finance information. Investors, regulation bodies and banks strive for higher standardization to provide accountability and to enter nonfinance factors in ratings and normative acts. Intensifying global attention to issues of climate change, diversity and inclusivity, as well as COVID-19 crisis accelerated this process. The article studies possible reasons, why companies provide voluntary non-finance information, in spite of potential costs and strategic after-effects. The problem is very important as serious efforts are taken to identify and generalize various theories, which specify corporate accountability making by companies. The author analyzed theories of revealing non-finance information in company reports.